Biphasic mineralized collagen-based composite scaffold for cranial bone regeneration in developing sheep. (18th January 2022) - Zheng, Jingchuan; Zhao, Zhijun; Yang, Yongdong; Wang, Shuo; Zhao, Yonggang; Xiong, Yang; Yang, Shuhui; Qiu, Zhiye; Song, Tianxi; Zhang, Chunyang; Wang, Xiumei
Abstract: Appropriate mechanical support and excellent osteogenic capability are two essential prerequisites of customized implants for regenerating large-sized cranial bone defect. Although porous bone scaffolds have been widely proven to promote bone regeneration, their weak mechanical properties limit the clinical applications in cranioplasty. Herein, we applied two previously developed mineralized collagen-based bone scaffolds (MC), porous MC ( p MC) and compact MC ( c MC) to construct a biphasic MC composite bone scaffold ( b MC) to repair the large-sized cranial bone defect in developing sheep. A supporting frame composed of c MC phase in the shape of tic–tac–toe structure was fabricated first and then embedded in p MC phase. The two phases had good interfacial bond, attributing to the formation of an interfacial zone. The in vivo performance of the b MC scaffold was evaluated by using a cranial bone defect model in 1-month-old sheep. The computed tomography imaging, X-ray scanning and histological evaluation showed that the p MC phase in the b MC scaffold, similar to the p MC scaffold, was gradually replaced by the regenerative bone tissues with comprehensively increased bone mineral density and complete connection of bone bridge in the whole region. The c MC frame promoted new bone formation beneath the frame without obvious degradation, thus providing appropriate mechanical protection and ensuring the structural integrity of the implant. In general, the sheep with b MC implantation exhibited the best status of survival, growth and the repair effect. The biphasic structural design may be a prospective strategy for developing new generation of cranioplasty materials to regenerate cranial bone defect in clinic. Graphical Abstract: